INVESTIGATIONS OF HEMOPROTECTING EFFECT OF ALGICLAM IN A CASE OF RADIATION AFFECT - T. V. Ponomareva; I. K. Romanovich (Радиационная гигиена)
Experimental investigations of hemoprotection effect of algiclam were carried out on not thoroughbred white rats of different sex (50 females and 50 males of the same age), exposured by sublethal dose. It was obtained that algiclam exert strongly radioprotection effect on the form elements of red blood and thrombocytes.The results obtained in the experiment allows to estimate in the better extent the influence of the modificators and indicates the real possibility of reducing or even averting of a number of hematological symptoms of emission effect with the help of biologically active food additive named algiclam.